Kinerja Implementasi Program Usaha Peningkatan Pendapatan Keluarga Sejahtera (Uppks) di Kecamatan Melati Kabupaten Sleman - Edison, Edison (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2014)
The issue of population growth has always had a strong relevance to the issue of public welfare. In orderto respond to these twin issues, National Family Planning Coordinating Board (BKKBN) consern totake part as an actor to empower families with the public education movement synchronizes continuouslyto conscious family planning and led to the stimulation of capital -prioritas on FP active, fertile couples,Uncategorized Pre-prosperous and prosperous I- stage for productive economic activity in order toachieve economic security of the family. The program known as Business Income Family Welfare(UPPKS). Studies of this UPKS program mengususkan settings Jasmine observations in District district.Sleman, Yogyakarta, the research question to be answered is in association with these objectives,the issues that will be explored in the study of program implementation UPPKS is